Normative Study of the Literacy Independent Cognitive Assessment in Illiterate and Literate Elderly Koreans - Kang, Seung-Gul; Cho, Seong-Jin; Ryu, Seung-Ho; Choi, Seong Hye; Han, Seol-Heui; Shim, Yong S.; Ko, Kwang-Pil; Jeong, Jee H.; Lee, Jun-Young; Lee, Dong Woo (Psychiatry investigation, 2015)
The aim of this study was to provide normative data on the Literacy Independent Cognitive Assessment (LICA) and to explore the effects of age, education/literacy, and gender on the performance of this test. Eight hundred and eighty-eight healthy elderly subjects, including 164 healthy illiterate subjects, participated in this study. None of the participants had serious medical, psychiatric, or neurological disorders including dementia. Bivariate linear regression analyses were performed to examine the effects of age, education/literacy, and sex on the score in each of the LICA cognitive tests. The normative scores for each age and education/literacy groups are presented. Bivariate linear regression analyses revealed that total score and all cognitive tests of the LICA were significantly influenced by both age and education/literacy. Younger and more-educated subjects outperformed older and illiterate or less-educated subjects, respectively, in all of the tests. The normative scores of LICA total score and subset score were presented according to age (60-64, 65-69, 70-74, 75-80, and ≥80 years) and educational levels (illiterate, and 0-3, 4-6, and ≥7 years of education). These results on demographic variables suggest that age and education should be taken into account when attempting to accurately interpret the results of the LICA cognitive subtests. These normative data will be useful for clinical interpretations of the LICA neuropsychological battery in illiterate and literate elderly Koreans. Similar normative studies and validations of the LICA involving different ethnic groups will help to enhance the dementia diagnosis of illiterate people of different ethnicities.